2013
DOI: 10.7556/jaoa.2013.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inpatient Electroencephalography on Clinical Decision Making

Abstract: In this study, inpatient EEGs rarely contributed to clinical decision making and in no case resulted in a change in diagnosis or management. These findings warrant future research on the effectiveness of inpatient EEGs for a wide breadth of clinical inpatient diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…The results of this study show that more males 89 (62.7%) than females 53 (37.3%) were referred for EEG and 84.5% of the patients were less than 30 years old. Preponderance of male referrals over females for EEG reported in this study is similar to reports from two previous Nigerian studies and studies from USA 9 11 , but differs from that of Pearce and Cock, from United Kingdom, which reported a preponderance of females over male referrals 8 . It has been reported that male preponderance may be a reflection of the fact that more male patients than females are affected by epilepsy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this study show that more males 89 (62.7%) than females 53 (37.3%) were referred for EEG and 84.5% of the patients were less than 30 years old. Preponderance of male referrals over females for EEG reported in this study is similar to reports from two previous Nigerian studies and studies from USA 9 11 , but differs from that of Pearce and Cock, from United Kingdom, which reported a preponderance of females over male referrals 8 . It has been reported that male preponderance may be a reflection of the fact that more male patients than females are affected by epilepsy.…”
Section: Discussionsupporting
confidence: 87%
“…The provisional diagnosis of the referring doctors in this study showed that epilepsy (79.5%) was the commonest reason for referral, (with 30.9% having specific or classified diagnosis and 48.6% unclassified diagnosis), cerebral palsy 8.5% and some other minor conditions. The finding from this study that epilepsy was the commonest reason for which patients were referred for EEG is similar to some other studies in Nigeria 9 , 10 , Africa 14 and Europe 12 but differs from result of a study from USA 11 . Harmon et al, reported that the commonest reason for EEG referral was altered mental status 52 (26%) followed by seizure 48 (24%) 8 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As expected, the EEG findings that were mainly associated with diagnosis and/or treatment change included electrographic seizures and interictal epileptiform discharges. In previous studies, EEGs confirmed diagnosis and altered management in 0–22% of the patients . Higher yield of abnormal findings and higher rates of contribution to making the diagnosis (42–100%) were reported in the emergent setting, when EEGs were performed for diagnosis of nonconvulsive and subtle status epilepticus, follow‐up of convulsive status epilepticus and suspected cerebral death in patients presented to the emergency department or admitted in intensive care units with altered mental states, although low rates of 5% and 10·7% of status epilepticus confirmation were reported in these patients as well .…”
Section: Discussionmentioning
confidence: 91%
“…2 EEG may assist in determining the underlying brain dysfunction and its severity in these patients, 3 given ample body of empirical evidence suggesting that different grades of background activity slowdown correlate with the functional severity of clinical encephalopathy. 4 However, when considering the prognostic correlation of an increasing background slowing, it is always important to perform activation procedures to test the reactivity, including eye opening, as well as response to sounds and painful stimulations. Even on a very slow EEG, a clear reactivity (regardless of either high voltage slowing or an acceleration with amplitude attenuation) heralds a better prognosis.…”
Section: Introductionmentioning
confidence: 99%